Genotype x Environment Interaction and Stability Analysis of Drought Tolerant Horse Gram [Macrotyloma uniflorum (Lam.) Verdc.] Accessions in Burkina Faso - Tuwendsida Joseph NANAMA; Antoine BARRO; Teyioué Benoit Joseph BATIÉNO; Zinmanké COULIBALY; Siaka TIAMA; Mirela Irina CORDEA (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Horticulture)
The recurrence of drought due to climate change is one of the major challenges facing agriculture in different parts of the world. Under-utilized or neglected species such as the horse gram [Macrotyloma uniflorum (Lam.) Verdc.] recognized for its potential tolerance and adaptability to drought, offers an alternative solution to this problem. However, it is unclear whether this tolerance and adaptability are stable from one environment to another, hence this study aimed to identify stable drought tolerant accessions under normal and stressful conditions. The experiments were conducted during the dry season using a Fisher block design with three replicates. Twenty-five (25) accessions were used as plant material for the study. The results of the combined analysis of variance revealed the presence of significant variability for most of the traits. The GGE double projection study revealed a similarity between the systems tested. It also made it possible to identify accessions specifically adapted to each regime for seed weight and seed yield. These were accessions HG54 and HG15 for the RI system and HG5 and HG44 for the RS system. These results offer a way forward for the development of a breeding research program to promote horse gram in Burkina Faso.